The psychological impact of the covid-19 quarantine on a group of adults peruvian - Angeles Donayre, Mariuccia (2020)
The objective was to determine the psychological impact of the COVID-19 quarantine in a group of Peruvian adults. It was a basic study, descriptive-correlational level, non-experimental design and cross-sectional. 35 subjects of both sexes participated, from 22 to 87 years old, both from Lima and the provinces. For this purpose, the Generalized Anxiety Disorder Scale (GAD-7) was used, which consists of 7 items from 0 to 3 (Likert type), which includes two aspects: symptoms and disability associated with the disorder. The results indicated that there is a feeling of anxiety among the surveyed subjects due to quarantine (45.7%) and with respect to the fact of staying home for quarantine, this appears as a protective factor against the anxiety experienced by the participants (OR = 0.084, 95% CI = 0.008 -0.839).